Phase field crack model with diffuse description for fracture problem and implementation in engineering applications. (March 2019) - Li, She; Tian, Li; Cui, Xiangyang
Highlights: Diffusion description for crack propagation is established by coupling displacement and phase field. Smoothed Galerkin weak form is presented for phase field fracture problems. The In-house code is embedded in ABAQUS with UEL/UMAT. A user-friendly graphical interface is developed for general users. Abstract: In this work, the phase-field modeling is formulated in the framework of cell-based smoothed finite element method for predicting the crack propagation in solids. Unlike the description of cracks as sharp surfaces, an exponential function is introduced to approximate the diffuse crack topology. The order parameter with continuous values changes from 0 to 1, which is employed to distinguish the broken and unbroken materials. The present modeling for crack propagation links damage and fracture mechanics. Every node on each element has two (or three) displacement and one phase-field DOFs. Cell-based smoothed finite element method is employed to solve the coupled elastic displacement and phase-field fracture problem. Several numerical tests are employed to validate the feasibility of present modeling. Numerical results obtained by the proposed modeling are in good accordance with the analytic one or the other methods. Meanwhile, the method can be easily embedded in the commercial software ABAQUS with user defined subroutines. In order to offer convenience for engineers, a user-friendly interface for ABAQUS is established based on Qt. One can establish input file conveniently without professional knowledge. Its attractive features produce potential for further study.